Cell-free culture conditioned medium elicits pancreatic β cell lineage-specific epigenetic reprogramming in mice - Kawamoto, Koichi (Oncol Lett, 2018)
There are several obstacles to overcome prior to achieving cellular reprogramming of pancreatic β cells in vitro and in vivo. The present study demonstrated that the transfer of epigenetic phenotypes was achieved in the cell-free conditioned medium (CM) of pancreatic insulinoma MIN6 cell cultures. The comparison of a subpopulation of MIN6, m14 and m9 cells indicated that MIN6-m14 cells were more prone to cellular reprogramming. Epigenetic profiling revealed that the transcription factor pancreas/duodenum homeobox protein 1 (Pdx1) was differentially associated among the clones. The culture of differentiated adipocytes in the CM of MIN6-m14 cells resulted in the induction of insulin mRNA expression, and was accompanied by epigenetic events of Pdx1 binding. The epigenetic profiling indicated that Pdx1 is preferentially associated with a previously uncharacterized region of the endoplasmic reticulum (ER) disulfide oxidase, ER oxidoreductin 1 gene. Therefore, the results of the present study indicated that the CM of MIN6 cells was able to induce a pancreatic β cell-like phenotype in differentiated adipocytes. These data provide additional support for the utility of cell-free CM for cellular reprogramming.